Ca2+高透過性TRPV6の粘膜バリア機能の調節を介した大腸炎に対する保護的役割 - 加藤, 伸一; 松本, 健次郎; 安田, 浩之; 田嶋, 鈴夏; 斉藤, 美知子 (日本薬理学会年会要旨集, 2023)
Transient receptor potential vanilloid 6 (TRPV6), which is a highly Ca2+-permeable cation channel, is expressed in gastrointestinal epithelia and implicated in maintaining Ca2+ homeostasis via transcellular Ca2+ transport. In this study, we investigated the local roles of TRPV6 in colonic mucosal barrier functions and pathogenesis of colitis in mice. Colitis was induced in TRPV6KO and wild-type (WT) mice by 7-days treatment with dextran sulfate sodium (DSS). Intestinal permeability was evaluated by FITC-dextran methods. The colonic mucus secretion determined histochemically, epithelial cell proliferation determined immunohistochemically, and expression of adherence and tight adherence junction proteins determined by western blotting were examined to evaluate the mucosal barrier functions. The severity of DSS-induced colitis was significantly aggravated in TRPV6KO mice compared with WT mice. Intestinal permeability was also significantly increased in TRPV6KO mice compared with WT mice even in normal conditions (without DSS). Although there is no difference in the colonic mucus secretion and epithelial cell proliferation between WT and TRPV6KO mice, the expression of adherence junction protein E-cadherin, and tight junction protein claudin-3 and occludin was significantly lower in TRPV6KO than WT mice in normal conditions. These findings suggest that TRPV6 plays a critical role in regulation of mucosal barrier functions via expression of adherence and tight junction proteins to protect against colitis.